Sentencing in Time - Meyer, Linda Ross (Amherst College Press, 2017)
Exactly how is it we think the ends of justice are accomplished by sentencing someone to a term in prison? How do we relate a quantitative measure of time-months and years-to the objectives of deterring crime, punishing wrongdoers, and accomplishing justice for those touched by a criminal act? Linda Ross Meyer investigates these questions, examining the disconnect between our two basic modes of thinking about time-chronologically (seconds, minutes, hours), or phenomenologically (observing, taking note of, or being aware of the passing of time). In Sentencing in Time, Meyer asks whether-in overlooking the irreconcilability of these two modes of thinking about time-we are failing to accomplish the ends we believe the criminal justice system is designed to serve. Drawing on work in philosophy, legal theory, jurisprudence, and the history of penology, Meyer explores how, rather than condemning prisoners to an experience of time bereft of meaning, we might instead make the experience of incarceration constructively meaningful-and thus better aligned with social objectives of deterring crime, reforming offenders, and restoring justice.